TANTANGAN DAN SOLUSI PELAKSANAAN PENDIDIKAN INKLUSIF DI SD/MI - Dewi Niswatul Fithriyah; Siti Kurniawati; Khofifah Indar Lutfiani; Luluk Nurul Aini; Septya Relan Alivia Nanda Baisroh; Muhammad Hasan Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education is an approach that provides opportunities for all students, including those with special needs, to receive an equal education within a single school environment. At the elementary school (SD) and Islamic elementary school (MI) levels, inclusive education plays a crucial role in instilling the principles of justice, tolerance, and respect for diversity from an early age. However, in practice, inclusive education in SD/MI still faces a number of challenges stemming from factors both inside and outside the school. This study aims to examine the challenges faced and find strategic solutions for the implementation of inclusive education in SD/MI. The method used is a literature review by analyzing various sources such as scientific journal articles, books, and policy documents related to the topic of inclusive education. The study revealed that internal challenges include a lack of teacher skills, inadequate facilities and infrastructure, a non-inclusive school culture, a curriculum that is not responsive to diversity, and suboptimal school management. External challenges, on the other hand, include low parental support, the impact of the social and cultural environment, and obstacles in implementing educational policies. Therefore, strategic solutions are needed, such as improving teacher competency, providing disability-friendly facilities, strengthening collaboration between schools, parents, and professionals, and providing ongoing policy support. This study is expected to serve as a reference in developing and improving the quality of inclusive education in elementary schools (SD/MI).